A court of wings and ruin ebook - Maas, Sarah J. (A Court of Thorns and Roses, 2017)
The epic third novel in the #1 bestselling Court of Thorns and Roses series by global phenomenon Sarah J. Maas. Feyre has returned to the Spring Court, determined to gather information on Tamlin's actions and learn what she can about the invading king threatening to bring her land to its knees. But to do so she must play a deadly game of deceit. One slip could bring doom not only for Feyre, but for everything-and everyone-she holds dear. As war bears down upon them all, Feyre endeavors to take her place amongst the High Fae of the land, balancing her struggle to master her powers-both magical and political-and her love for her court and family. Amidst these struggles, Feyre and Rhysand must decide whom to trust amongst the cunning and lethal High Lords, and hunt for allies in unexpected places. In this thrilling third book in the #1 bestselling series from Sarah J. Maas, the fate of Feyre's world is at stake as armies grapple for power over the one thing that could destroy it.